2021
DOI: 10.1007/s13187-021-02020-3
|View full text |Cite
|
Sign up to set email alerts
|

Shortening the Frommelt Attitude Toward the Care Of the Dying Scale (FATCOD-B): a Brief 9-Item Version for Medical Education and Practice

Abstract: End-of-life care training has gaps in helping students to develop attitudes toward caring for the dying. Valid and reliable assessment tools are essential in building effective educational programmes. The Frommelt Attitude Toward the Care Of the Dying scale (FATCOD-B) is widely used to measure the level of comfort/discomfort in caring for the dying and to test the effectiveness of end-of-life care training. However, its psychometric properties have been questioned and different proposals for refinement and sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
(65 reference statements)
1
6
0
Order By: Relevance
“…Thus, in Spain, although the different centers teach content regarding palliative care, there is a disparity in the content and credit depending on the university of origin [ 14 ]. On the other hand, together with one’s formal education [ 30 , 31 ], it should be taken into account that the nurse must maintain, as indicated in the Code of Ethics of the ICN (International Council of Nurses), the responsibility of the practice and maintain competence through continuous learning [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in Spain, although the different centers teach content regarding palliative care, there is a disparity in the content and credit depending on the university of origin [ 14 ]. On the other hand, together with one’s formal education [ 30 , 31 ], it should be taken into account that the nurse must maintain, as indicated in the Code of Ethics of the ICN (International Council of Nurses), the responsibility of the practice and maintain competence through continuous learning [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The recently released FATCOD-9IT 26 was checked in this study to test scale functioning and reliability, item scalability and capability to differentiate respondents with different levels of attitudes and to discriminate among students at different stages of medical training (preclinical vs clinical). The five research hypotheses specifying the aim of the study were all confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…The FATCOD-9IT is a brief self-administered questionnaire scored on a 5-point Likert-type scale (from 1 = “totally disagree” to 5 = “totally agree”) developed by the authors as a result of the progressive modelling of the original 30-item version 17 recently released. 26 Considering item content and answer scale, answering agreement indicates aversion, thus in its form the summed score measures inaptitude toward the care of the dying.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FATCOD- Form B Scale English version was used to assess the students’ attitudes toward caring for dying patients [ 21 ]. FATCOD-B consists of 9 items on a 5-point Likert scale Ranging from 1 to 5, where 1 = “ strongly disagree ”, 2 = “ disagree ”, 3 = “ uncertain ”, 4 = “ agree ”, 5 = “ strongly agree ”.…”
Section: Methodsmentioning
confidence: 99%